The internet dilemma: An exploratory study of luxury firms' usage of internet-based technologies. (March 2018) - Baker, Jeff; Ashill, Nick; Amer, Noha; Diab, Ekram
Abstract: Surprisingly, there exists a paucity of research examining the adoption of Internet-based technologies by luxury firms. This represents a major shortcoming in our understanding of how luxury firms maintain the image of their brand, sustain a personal link with customers, and retain an aura of exclusivity as they seek to provide their products and services to increasingly technologically-astute customers. Using content analysis, we present the findings of a qualitative investigation of 92 luxury firm websites across the categories of automobiles, fashion, jewelry, watches, and yachts. Study findings indicate that there are noticeable differences in website characteristics and functionality across sectors. Implications of the results are discussed, noting that decisions about using the Internet for branding and selling, one-way and two-way communications, as well as operational and innovative features, are driven by the characteristics of the products being offered. Avenues for future research are also offered.